ANALISIS RISIKO PENYEBAB KETERLAMBATAN PROYEK PENGEMBANGAN PEMBANGUNAN GEDUNG MARGONO SURADJI YOGYAKARTA BERBASIS PMBOK - Novika Candra Fertilia; Sediyanto Sediyanto; Ahmad Fuadi (Construction and Material Journal, 2023)
The expansion of industry and the growth of development facilities in Indonesia is very rapid, especially the construction of buildings. Then the level of difficulty to manage and run a building project is getting higher. The higher level of difficulty, the longer the duration of time required to complete the project. Even though an activity has been planned as well as possible, it still contains uncertainty that it will run fully according to the plan. This happened to the building construction project in Yogyakarta, where the project experienced a delay of 35%. This study aims to find out the causes that have a high influence on the delay in the project. In this study, the influence value category was calculated using the project risk management calculation approach based on the 2017 PMBOK.